2005
DOI: 10.1111/j.1365-2265.2005.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plasminogen activator inhibitor‐1 gene 4G/5G polymorphism on glucose and lipid metabolisms in Turkish obese children

Abstract: Although the frequency of the 4G/4G genotype was higher in subjects in the current study than in subjects reported in the literature, in our study group we observed no influence of the PAI-1 4G/4G polymorphism on lipid and glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
8

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
1
0
8
Order By: Relevance
“…In Children with obesity, Estelles et al [ 39 ] observed no influence of the 4 G/5 G polymorphism on PAI-1 levels. Moreover, no influence of the PAI-1 4 G/5 G polymorphism on lipid and glucose metabolism parameters was observed in Turkish obese children [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Children with obesity, Estelles et al [ 39 ] observed no influence of the 4 G/5 G polymorphism on PAI-1 levels. Moreover, no influence of the PAI-1 4 G/5 G polymorphism on lipid and glucose metabolism parameters was observed in Turkish obese children [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Τα αποτελέσματά μας συμφωνούν όσον αφορά τη συχνότητα του γονότυπου 4G/4G και με άλλη μελέτη όπου σε 39 παχύσαρκα παιδιά και 38 υγιείς μάρτυρες η συχνότητα του γονότυπου 4G/4G ήταν σημαντικά υψηλότερη στα παχύσαρκα παιδιά από ό, τι στους μάρτυρες (4,280). Βέβαια, υπάρχει συζήτηση σχετικά με την αυξημένη συχνότητα του πολυμορφισμού 4G/5G(rs1799762) στην παχυσαρκία.…”
Section: συζητησηunclassified
“…Επίσης, καμία σημαντική διαφορά δεν βρέθηκε μεταξύ παχύσαρκων παιδιών και μαρτύρων αναφορικά με την κατανομή της συχνότητας του γονότυπου 4G/5G (6). Αν και στη μελέτη των Kinik και συν, δεν χρησιμοποιήθηκε ομάδα ελέγχου, διαπιστώθηκε υψηλότερη συχνότητα του γονότυπου 4G/4G σε παχύσαρκα παιδιά σε σχέση με τις δύο παραπάνω μελέτες (280). Υπάρχουν δύο μελέτες σχετικά με τον πολυμορφισμό 4G/5G(rs1799762) σε υγή τουρκικό πληθυσμό αλλά χωρίς πληροφορίες για το ΔΜΣ τους (266,301).…”
Section: συζητησηunclassified
See 2 more Smart Citations